Pockets of resistance : British news media, war and theory in the 2003 invasion of Iraq. - Robinson, Piers (Manchester International Relations, 2016)
For scholars of media and war, the 2003 invasion of Iraq is a compelling case to study. As part of President Bush's 'war on terror', the invasion was the most controversial British foreign policy decision since Suez, and its ramifications and aftermath have rarely been far from the news. In the many political and public debates regarding this conflict, arguments over the role of the media have been omnipresent. For some, media coverage was biased against the war, for others it became a cheerleader for the invasion. Where does the truth lie? Drawing upon a uniquely-detailed and rich content and.